Soil loss and runoff in southern Brazil in conservation systems: a long-term experiment - Dambros, Liana; Lima, Luciana da Silva Corrêa; Barros, Claudia Alessandra Peixoto de; Cassol, Elemar Antonino (Acta Scientiarum. Agronomy, 2023)
Brazil has high soil loss rates due to its tropical and subtropical climate characteristics. In this sense, soil use and management practices may minimize such losses. In this study, experimental plots were monitored for eight years in southern Brazil during natural rainfall events. Treatments were as follows: I) bare soil under conventional tillage, II) barley-oat/ soybeans succession under conventional tillage, III) oat-lupine-vetch/ maize succession under conventional tillage, IV) barley-oat/ soybeans succession under no-tillage, and V) oat-lupine-vetch/ maize succession under no-tillage. Data on rainfall amount and erosivity indices (EI30, EI20, and EI10) were subjected to regression analyses, evaluating the effects of climatic variables on soil and water losses. We could also analyze crop species, conventional and no-tillage systems, and winter and summer seasons. The highest soil and water losses occurred in treatments under conventional tillage. In addition, soybeans treatments increased soil and water losses. Maize under no-tillage was the most efficient practice, as it had soil losses (3.4 times) and water losses (1.5 times) lower than soybeans under conventional tillage. Rainfall amounts and EI30 were better correlated with soil and water losses in conventional tillage treatments. However, EI10 could better explain the soil losses from the conservationist treatment.